Development of a pHrodo-based assay for the assessment of in vitro and in vivo erythrophagocytosis during experimental trypanosomosis. - Benoit Stijlemans; Jennifer Cnops; Peter Naniima; Axel Vaast; Viki Bockstal; Patrick De Baetselier; Stefan Magez (Public Library of Science (PLoS), 2015)
Extracellular trypanosomes can cause a wide range of diseases and pathological complications in a broad range of mammalian hosts. One common feature of trypanosomosis is the occurrence of anemia, caused by an imbalance between erythropoiesis and red blood cell clearance of aging erythrocytes. In murine models for T. brucei trypanosomosis, anemia is marked by a very sudden non-hemolytic loss of RBCs during the first-peak parasitemia control, followed by a short recovery phase and the subsequent gradual occurrence of an ever-increasing level of anemia. Using a newly developed quantitative pHrodo based in vitro erythrophagocytosis assay, combined with FACS-based ex vivo and in vivo results, we show that activated liver monocytic cells and neutrophils as well as activated splenic macrophages are the main cells involved in the occurrence of the early-stage acute anemia. In addition, we show that trypanosomosis itself leads to a rapid alteration of RBC membrane stability, priming the cells for accelerated phagocytosis.